Metafora Kata Buah dalam Bahasa Melayu Dialek Mempura Kabupaten Siak: Kajian Semantik Kognitif - Afriliyani Safitri; Hermandra Hermandra; Mangatur Sinaga (Balai Bahasa Provinsi Riau, 2020)
AbstractMetaphor becomes a marker of language in Malay society. Metaphors are usually used to praise, insinuate, ask for, and express something. Therefore, it is necessary to conduct an analysis study of the metaphor of the word fruit in Mempura Malay language as physical parts and space of human body to reveal the meanings. The purpose of this research is to find out the metaphorical forms and meanings of the word fruit as the physical parts and space of human body in Mempura Malay language. This qualitative and descriptive research was conducted through a cognitive semantic perspective. The data of this research were collected from the utterances of the Mempura Malay community which mostly used metaphorical expressions. The techniques of data collection were by means of interviewing, evoking, listening and conversation, and recording. The data were analyzed by means of descriptive method. The result of the study shows that there are several metaphors for the word fruit as the physical parts and space of human body in Mempura Malay language to express something such as ‘buah hati’, ‘buah jakun’, ‘buah betis’, ‘buah dada’, and ‘buah cinta’. AbstrakMetafora menjadi penanda bahasa dalam masyarakat Melayu. Metafora biasanya digunakan untuk memuji, menyindir, meminta, dan menyatakan sesuatu. Hal ini mendorong dilakukan analisis metafora kata buah bagian fisik dan ruang manusia untuk mengetahui makna ungkapan yang terdapat dalam bahasa Melayu Mempura. Tujuan dari penelitian ini adalah menemukan bentuk dan makna metafora kata buah bagian fisik dan ruang manusia dalam bahasa Melayu Mempura. Metode yang digunakan ialah metode penelitian deskriptif kualitatif melalui perspektif semantik kognitif. Data penelitian ini diambil dari tuturan masyarakat Melayu Mempura yang banyak menggunakan ungkapan metafora. Teknik yang digunakan dalam mengumpulkan data adalah teknik wawancara yang dibantu dengan teknik pancing, dan simak cakap yang disertai dengan teknik rekam. Teknik analisis data dilakukan menggunakan metode deskriptif. Hasil penelitian menunjukkan bahwa terdapat metafora kata buah bagian fisik dan ruang manusia dalam bahasa Melayu Mempura untuk menyatakan sesuatu, misalnya, buah hati, buah jakun, buah betis, buah dada, buah cinta, dan lain sebagainya.